Temperature-independent refractometer based on a tapered photonic crystal fiber interferometer - Ni, Kai (2013)
A temperature-independent refractometer by using a tapered photonic crystal fiber (PCF) based Mach–Zehnder interferometer (MZI) is proposed and experimentally demonstrated. It is fabricated by sandwiching a tapered PCF of 29 mm long between two standard single mode fibers (SMFs) with the fully collapsed air holes of the PCF in the fusion splicing region. It has been found that tapering the PCF greatly enhances the sensitivity of the refractometer. A maximum sensitivity of 1529 nm/RIU (refractive index unit) is achieved within the range from 1.3355 to 1.413. The refractometer is nearly temperature-insensitive due to the ultra low temperature dependence of the used.